2011
DOI: 10.1007/s11205-011-9883-9
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural Dispositions and Wellbeing of the Women Left Behind: A Case of Migrant Households in Nepal

Abstract: The concept of wellbeing is gaining popularity in the study of quality of life and cultural significance of living. The paper aims to contribute to our understanding of objective and subjective wellbeing by exploring the perceptions of women left behind by out-migrating husbands on their quality of life in a transnational social field. The paper uses both qualitative and quantitative research methods. Its primary focus is on the life stories of the four women left behind by their migrant husbands, complementin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 34 publications
(63 reference statements)
4
47
2
Order By: Relevance
“…Their findings suggested neglect of subsistence farming with access to alternative sources of income and a preference for livestock raising over crop farming. Other studies have found increasing feminization of the agricultural sector, and an increasing workload for women, but also signs of empowerment (Gartaula et al 2010;Adhikari and Hobley 2011;Gartaula et al 2012b;Sharma and Thapa 2013;Tamang et al 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Their findings suggested neglect of subsistence farming with access to alternative sources of income and a preference for livestock raising over crop farming. Other studies have found increasing feminization of the agricultural sector, and an increasing workload for women, but also signs of empowerment (Gartaula et al 2010;Adhikari and Hobley 2011;Gartaula et al 2012b;Sharma and Thapa 2013;Tamang et al 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Rather, food security is associated with the capability of people to exercise foodrelated choices and enhance their social wellbeing. The concept of social wellbeing embraces both objective and subjective aspects of food security [39,40], which relates to the availability of food, access to food and the ability to use and make effective choices for food and livelihood [41]. The objective dimension of food security emphasizes the ends, or physical availability of food and its ability to meet caloric requirements of individuals in a population.…”
Section: A Critical Assessment Of the Three Approaches With Referencementioning
confidence: 99%
“…This is perhaps due to their lower social status, which cannot be easily changed by a higher monthly income in caste-based rural Indian society. Studies have shown that while a higher household income is helpful in increasing wellbeing up to a certain point, it becomes less significant in terms of increasing long-term life satisfaction [40,52]. Simply put, money does not always play a significant role in contributing to greater wellbeing; other social, cultural and interpersonal factors do also matter.…”
Section: Wellbeing: the Role Of Agricultural And Off-farm Livelihood mentioning
confidence: 99%
“…The decision is a collective one that involves the extended family and is driven by the opportunity of remittances for those left behind. [7][8][9][10] Migration and health researchers cite the complexity of migration on family members left behind. Globally, studies have identified health disparities among women with migrant husbands 11 and negative consequences of migration on other family members' health, 12 children's education, 13 and child wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some wives reported that their mothers-in-law made decisions regarding when a woman with a migrant husband should visit a doctor, attend antenatal care, and who is to accompany them on clinic visits related to their reproductive health. 10 The cultural impact of migration on women's roles is suggested to have rendered women with migrant husbands " … invisible, and their role, experience, well-being, and interconnectedness with the practice of migration are not well understood" 10,22,23 Migration often challenges traditional roles of women at home, as the increased workload for women and dependence on remittances alters the expectations of autonomy and decision-making power. 24 Understanding women's reproductive health and related household decision-making may provide insights on how they manage changing dynamics with inlaws in their husbands' absence.…”
Section: Introductionmentioning
confidence: 99%